2013
DOI: 10.1007/s10571-013-9923-x
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Activity in Human Brain Tumors: Astrocytoma and Meningioma

Abstract: Somatic cells do not have telomerase activity but immortalized cell lines and more than 85 % of the cancer cells show telomerase activation to prevent the telomere from progressive shortening. The activation of this enzyme has been found in a variety of human tumors and tumor-derived cell lines, but only few studies on telomerase activity in human brain tumors have been reported. Here, we evaluated telomerase activity in different grades of human astrocytoma and meningioma brain tumors. In this study, assay fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
1
18
0
2
Order By: Relevance
“…The study objectives were categorized as genetic (n = 9 articles [38, 44, 50, 56, 62, 6566, 70–71], 449 patients), epidemiologic (n = 7 articles [47, 49, 6061, 63, 69, 74], 13,193 patients), pathologic (n = 7 articles [46, 48, 52, 55, 67–68, 72], 4,365 patients), clinical (n = 6 articles [39, 41, 43, 45, 57, 76], 393 patients), radiologic (n = 4 articles [, 86 patients), radiotherapy (n = 3 articles [54, 5859, 73], 54 patients), surgical (n = 2 articles [42, 51], 44 patients), or virologic [75] (n = 1, 58 patients).…”
Section: Resultsmentioning
confidence: 99%
“…The study objectives were categorized as genetic (n = 9 articles [38, 44, 50, 56, 62, 6566, 70–71], 449 patients), epidemiologic (n = 7 articles [47, 49, 6061, 63, 69, 74], 13,193 patients), pathologic (n = 7 articles [46, 48, 52, 55, 67–68, 72], 4,365 patients), clinical (n = 6 articles [39, 41, 43, 45, 57, 76], 393 patients), radiologic (n = 4 articles [, 86 patients), radiotherapy (n = 3 articles [54, 5859, 73], 54 patients), surgical (n = 2 articles [42, 51], 44 patients), or virologic [75] (n = 1, 58 patients).…”
Section: Resultsmentioning
confidence: 99%
“…Among of them, 85% of tumor cells are positively correlated with the activity of telomerase. As a result, considering the telomerase activity as tumor, therapeutic targets has attracted numerous attentions in contemporary medicine science [37] [38]. Xiao et al [39] imported the different doses of litchi water extract to investigate the anti-hepatoma effects and results showed that litchi water extract reduces significantly the ratio of liver tumor with a negative telomerase activity simultaneously.…”
Section: Regulating the Activity Of Telomerasementioning
confidence: 99%
“…Pistolesi and colleagues, examining the case of an adult patient with RIM and multiple recurrences and metastases, demonstrated an increased expression of p53 and increased telomerase activity [52]. Although benign meningiomas have an overall lower telomerase activity, patients with Grade I meningiomas with an increased level of activity are at a greater risk of tumor recurrence even after GTR and, therefore, are more likely to require postoperative adjuvant radiation [53, 54]. Patients with high grade RIMs or those with multiple recurrences have been shown to have an increased vascularity and high levels of vascular endothelial growth factor (VEGF) mRNA expression as well; the expression of VEGF increases the risk of peritumoral edema, particularly following SRS [52, 55, 56].…”
Section: Molecular and Genetic Markersmentioning
confidence: 99%